Writing for Relief in Late Nineteenth-Century Dublin: Personal Applications to the Mansion House Fund in 1880. (20th October 2017) - Crossman, Virginia
Abstract: Focusing on a collection of personal applications made to the Dublin Mansion House Fund in 1880, this article explores the perception and experience of poverty and distress in late nineteenth-century Dublin. Despite the recent expansion of welfare history in Ireland, historians have been slow to examine urban poverty from the perspective of the poor. The article discusses some available sources and assesses the insights such material can provide into the situations facing and strategies adopted by the poor and vulnerable.